ANALYSIS OF THE INFLUENCE OF FINANCIAL LITERACY, FINANCIAL INCLUSION, AND LIFESTYLE ON THE FINANCIAL BEHAVIOR OF GENERATION Z - Fitriani Fitriani; Rismawati Rismawati; Imam Pribadi; Muhammad Aqsa; Duriani Duriani, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2024)
This lesson seeks to explore the impact of each variable that is used as the topic of this lesson. This learning takes a quantitative approach using survey techniques was used, involving 200 respondents from Generation Z. Data were collected through online questionnaires and analyzed from multiple linear regression. The results describe whether each variable is independent, both individually and collectively, significantly effect the financial behavior of Generation Z. Financial literacy presents a total regression coefficient of 0.208, with a total t of 2.765 and sign 0.007, demonstrating a positive and significant effect. Similarly, financial inclusion has a regression total coefficient 0.267, total t value 2.651, and sign 0.009, also reflecting a positive and significant influence. Lifestyle has a regression coefficient of 0.274 with a t-value of 2.693 and a significance of 0.008, indicating a significant and positive influence. This study suggests the enhancement of financial literacy programs, the expansion of financial inclusion, and better management of lifestyle in order to achieve future funding stability.